Self-reported Barriers to Regular Dental Care in Chennai, Tamil Nadu - Nandhini, L; Barani, K; Prabu, D; Manipal, Sunayana; Ahmed, Adil; Adusumilli, Preethi (Journal of Orofacial Research, 2013)
Aim: The aim of this study was to assess the self-reported barriers to regular dental care in Chennai city, Tamil Nadu. Materials and methods: The cross-sectional study was done on 352 people, aged 18 to 60 years in Chennai, Tamil Nadu. The study included 154 males and 196 females. The samples were selected by stratified random sampling and a 10 item questionnaire was given. Level of significance was set at <0.005, with 5% alpha error and 95% confidence interval. Results: Factor analysis revealed the factors of barriers which were daily brushing, practical reasons, unpleasant experiences, laziness and lack of appreciation. Sex showed significant correlation with reasons preventing daily brushing. The more educated the patients were the fewer barriers they had related to unpleasant experiences and factors of appreciation and laziness. The older people had more barriers relating practical reasons. Conclusion: The most significance reasons found were lack of knowledge, lack of interest, long distance to a particular dentist, restraint work.